Nonlinear Acoustic Echo Cancellation Using a Nonlinear Postprocessor With a Linearly Constrained Affine Projection Algorithm - Lee, Keunsang; Baek, Yonghyun; Park, Youngcheol (IEEE transactions on circuits and systems. II, Express briefs, 2015)
This brief presents a nonlinear acoustic echo cancellation algorithm comprising a postprocessor that can model the saturation-type nonlinear distortion of a microphone circuit. To support fast adaptation to the acoustic echo environment, the linear filter is adapted using an affine projection algorithm where the reference input vectors subject to linear operation are dynamically selected to update the coefficient vector. We consider the hard-clipper and sigmoid functions for the postprocessor, and their parameters are adaptively updated using the least-mean-square algorithm. The simulation results confirm that the proposed algorithm achieves fast and stable convergence under saturation-type microphone distortion, and it can have better performance than conventional algorithms.